(untitled) (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Marriage is an important institution in Islam that has specific rules in its implementation, including regarding the ijab qabul (consent to marriage). However, in practice there are differences among the Darul Istiqamah community, namely that it is carried out without the ijab qabul as in general. This study aims to analyze the phenomenon of marriage without ijab qabul in the Darul Istiqamah Islamic Boarding School community in Sinjai Regency from the perspective of understanding the hadith. This article uses an empirical legal method analyzed with a fiqh hadith approach (understanding of hadith). Data were collected through in-depth interviews with religious leaders, academics, and couples undergoing marriage. In addition, observation and analysis of documents such as journal articles, books, and literature related to the discussion. This study found that the understanding of the hadiths of the Prophet PBUH regarding the ijab qabul in a marriage among the Darul Istiqamah community who carry out marriages without ijab qabul differs from what is practiced in the Islamic community in general. The marriage practice carried out at the Darul Istiqamah Islamic Boarding School is by representing the guardian to the leadership and administrators of the Islamic Boarding School. In the context of understanding the hadith based on the history of Ummu Salamah regarding the marriage of Ali bin Abu Talib and Fatimah. This practice is based on the opinion of Imam Abu Hanifa in the ahlu sunnah wa aljama’ah school of thought, that not even a wali is allowed as long as he is equal and fulfills other requirements. Even though this practice is not common in Indonesia, which mostly follows the Imam Shafi’i school of thought, this is not contrary to Islamic law.